Crows control working memory before and after stimulus encoding - Erica Fongaro (Nature Portfolio, 2020)
Abstract The capacity of working memory is limited and this limit is comparable in crows and primates. To maximize this resource, humans use attention to select only relevant information for maintenance. Interestingly, attention-cues are effective not only before but also after the presentation of to-be-remembered stimuli, highlighting control mechanisms beyond sensory selection. Here we explore if crows are also capable of these forms of control over working memory. Two crows (Corvus corone) were trained to memorize two, four or six visual stimuli. Comparable to our previous results, the crows showed a decrease in performance with increasing working memory load. Using attention cues, we indicated the critical stimulus on a given trial. These cues were either presented before (pre-cue) or after sample-presentation (retro-cue). On other trials no cue was given as to which stimulus was critical. We found that both pre- and retro-cues enhance the performance of the birds. These results show that crows, like humans, can utilize attention to select relevant stimuli for maintenance in working memory. Importantly, crows can also utilize cues to make the most of their working memory capacity even after the stimuli are already held in working memory. This strongly implies that crows can engage in efficient control over working memory.